2022
DOI: 10.3389/fonc.2022.844144
|View full text |Cite
|
Sign up to set email alerts
|

ITGA5 Is a Novel Oncogenic Biomarker and Correlates With Tumor Immune Microenvironment in Gliomas

Abstract: Gliomas are the most aggressive primary intracranial malignancies with poor overall survival. ITGA5 is one member of the integrin adhesion molecule family and is implicated in cancer metastasis and oncogenesis. However, few studies have explored the association between tumor immune microenvironment and ITGA5 expression level in gliomas. Firstly, we analyzed 3,047 glioma patient samples collected from the TCGA, the CGGA, and the GEO databases, proving that high ITGA5 expression positively related to aggressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…ITGa5 forms a complex with ITGβ1 and is responsible for tumour cell migration and invasion. According to a recent study, this gene is involved in essential oncological pathways and is responsible for typical genomic alterations in gliomas, including the tumour immune microenvironment formation [53]. ITGβ1 showed a strong trend to be downregulated by ASC-EVs in U87 MG.…”
Section: Discussionmentioning
confidence: 99%
“…ITGa5 forms a complex with ITGβ1 and is responsible for tumour cell migration and invasion. According to a recent study, this gene is involved in essential oncological pathways and is responsible for typical genomic alterations in gliomas, including the tumour immune microenvironment formation [53]. ITGβ1 showed a strong trend to be downregulated by ASC-EVs in U87 MG.…”
Section: Discussionmentioning
confidence: 99%
“…Researching the molecular biomarkers and unique immunological status of gliomas has a profound effect on cancer diagnosis and therapeutic strategies. New studies have found that some biomarkers, such as ITGA-5 and Tenascin-C, could predict glioma prognosis, and are closely related to the immunosuppressive microenvironment, particularly for the clinical application of immunotherapy in glioma ( 26 , 27 ). New studies also reported that DDOST could interact with the microenvironment of gliomas and was negatively related to tumor-infiltrating B cells and CD4+ T cells and positively related to CAFs and tumor-associated macrophages (TAMs).…”
Section: Discussionmentioning
confidence: 99%
“…ITGA5 also tightly connect with IC molecules, which may benefit from IC blockade strategies. 50 Lysosome associated membrane glycoprotein 3 (LAMP3), belonging to the LAMP protein family, is overexpressed in a variety of cancers in which it is related to an unsatisfactory prognosis and may be pivotal for tumor metastasis. 51 Matrix metalloproteinase 14 (MMP14) is a membrane-type MMP, and the enhanced MMP14 activity is frequently associated with malignancy and is thought to promote metastasis.…”
Section: Discussionmentioning
confidence: 99%